(untitled) (World Economics and Finance Bulletin, 2024)
The current research aims to identify the use of artificial intelligence practices with its dimensions of (expert systems, automatic learning, intelligent agent, knowledge representation and reasoning) in digital marketing with its dimensions of (retention, learning, absorption, attraction) to serve the banking sector in a sample of private banks in Baghdad. To come up with a set of recommendations that contribute to improving their practice and adoption of these variables, and based on the modernity of the variables and their importance to the banking sector on the one hand, and society on the other hand, the research was applied in a sample of private banks in Baghdad Governorate to be the field from which data on the research variables are collected, for the purpose of analysis. Reaching results and achieving research objectives. For this purpose, a questionnaire was prepared that collects the research variables, consisting of (32) items, based on previous standards and models. In order to analyze the data obtained from the research questionnaire, which formed the opinions and answers of the sample, the researcher used the software (SPSS) to analyze the primary data, and the research adopted a descriptive approach. Analytical in completing his research, both its applied and theoretical sides, the statistical analysis showed a number of results, the most notable of which was the acceptance of all hypotheses, and it became clear that there is a link between artificial intelligence and digital marketing